ANALISIS KONSEKUENSI KEBAKARAN DAN LEDAKAN AKIBAT KEBOCORAN TABUNG LPG 50 KG PADA RESTORAN DI KELURAHAN JATIWARINGIN DENGAN PERANGKAT LUNAK ALOHA TAHUN 2022 - Anida Khairina (2022)
During 2017-2021, cases of explosions and fires caused by leakage of LPG cylinders 50 kg in Indonesia was continued, most of them occurred in restaurants. Jatiwaringin Sub-District in Bekasi City which has many restaurants which are generally located side by side with residential areas and public facilities, as well as a fire-prone area. If there is a fire and explosion due to leakage of LPG cylinder 50 kg, then the bad impact that occurs will be felt by many parties. This study aims to analyze the consequences of fires and explosions due to leakage of LPG cylinders 50 kg at restaurants in Jatiwaringin Sub-District with ALOHA software in 2022. This research is a descriptive study using purposive sampling with observation and interview sheets for the research instrument. The maximum threat zone is generated by BLEVE/fireball from propane's simulation for Restaurant A is 113 meters, Restaurant B is 141 meters, Restaurant C is 176 meters, Restaurant D is 201 meters, and butane for Restaurant A is 113 meters, Restaurant B is 140 meters, Restaurant C is 175 meters, Restaurant D is 199 meters. The restaurants can create and disseminate fire emergency response to workers and public around in loss prevention.